Sistemas Axiológicos del siglo XXI: Un collage. El declive de los sistemas axiológicos de creencias y la coexistencia de creencias variopintas en el mercado espiritual - DOI: 10.5752/P.2175-5841.2012v10n28p1295 - Prat-i-Pubill, Queralt (Horizonte, 2012)
We aim at showing why axiological systems coming from religion are not operative currently. To do this we show World Bank data where it is manifested that heteronomous systems of beliefs are not in force to orient the personal and social life of the individuals. We also communicate the declining numbers of those that register themselves as believers and we also reveal that there is no relationship between registering oneself as a believer in an axiological system and effectively holding and “believing” the beliefs of that axiological system. We clarify the common use of the term belief as a non-critical assumption, and other uses of the term in natural language and scientific language. We use statistical data for Catalonia, Spain and some countries of Europe and America. We conclude by asking if individuals’ axiological systems are not determined by religions, then What axiological systems do we have able to cohere and motivate individuals towards valuable common futures?